Habits, sentiment and predictable income in the dynamics of aggregate consumption - Martin Sommer (The Johns Hopkins University, Department of Economics, 2001)
This paper explores whether habit formation in the representative agent's preferences can explain two failures of the standard permanent income model with intertemporally separable utility: the sensitivity of consumption to lagged consumer sentiment and to predictable changes in current income I show that in a habit formation model the sensitivity of consumption growth to predicted income can be to a large extent reinterpreted as a sluggish response of consumption to news Moreover the sensitivity of consumption growth to lagged sentiment merely reflects the serial corre-lation in consumption growth generated by habits I study the model's predictions for the effect of the recent tax cut on aggregate consumption Contrary to the PIH model consumers with habits respond to permanent tax cuts slowly The estimated model predicts an immediate (first-quarter) MPC out of the permanent tax cut of only 30%.
Keywords: E10; E21; H31; 330; consumer sentiment; excess sensitivity; habit formation; consumption; marginal propensity to consume; tax cuts; Einkommenshypothese; Gesamtwirtschaftlicher Konsum; Konsumtheorie; Theorie